2007
DOI: 10.1016/j.bbabio.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

PPARα-activation results in enhanced carnitine biosynthesis and OCTN2-mediated hepatic carnitine accumulation

Abstract: In fasted rodents hepatic carnitine concentration increases considerably which is not observed in PPAR alpha-/- mice, indicating that PPAR alpha is involved in carnitine homeostasis. To investigate the mechanisms underlying the PPAR alpha-dependent hepatic carnitine accumulation we measured carnitine biosynthesis enzyme activities, levels of carnitine biosynthesis intermediates, acyl-carnitines and OCTN2 mRNA levels in tissues of untreated, fasted or Wy-14643-treated wild type and PPAR alpha-/- mice. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 27 publications
8
85
0
Order By: Relevance
“…These compounds activate PPAR␣, a lipid-sensing nuclear receptor that functions as a master regulator of fatty acid metabolism. Recent studies in PPAR␣ null mice confirmed an essential role for this nuclear receptor in regulating carnitine homeostasis, because these animals have a profound systemic carnitine deficiency associated with reduced hepatic expression of OCTN2 and ␥-butyrobetaine hydroxylase-1 (35,36). Consistent with these reports, short term high fat feeding (4 days), which activates the PPAR network, increases systemic carnitine levels (34,37).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These compounds activate PPAR␣, a lipid-sensing nuclear receptor that functions as a master regulator of fatty acid metabolism. Recent studies in PPAR␣ null mice confirmed an essential role for this nuclear receptor in regulating carnitine homeostasis, because these animals have a profound systemic carnitine deficiency associated with reduced hepatic expression of OCTN2 and ␥-butyrobetaine hydroxylase-1 (35,36). Consistent with these reports, short term high fat feeding (4 days), which activates the PPAR network, increases systemic carnitine levels (34,37).…”
Section: Discussionsupporting
confidence: 73%
“…Other clinical factors that disrupt carnitine status include renal dysfunction and use of drugs that form carnitine conjugates (32,33). Conversely, compounds belonging to the fibrate class of hypolipidemic drugs raise systemic carnitine levels, in parallel with increased hepatic expression of the carnitine biosynthetic machinery (34,35). These compounds activate PPAR␣, a lipid-sensing nuclear receptor that functions as a master regulator of fatty acid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic and intestinal carnitine levels are increased after PPAR␣ agonist (clofibrate and Wy14643) treatment of rodents and pigs (van Vlies et al, 2007;Ringseis et al, 2008). Increased carnitine levels are due to enhanced carnitine biosynthesis and uptake (Ringseis et al, 2008).…”
Section: Peroxisome Proliferator-activated Receptormentioning
confidence: 99%
“…2007) and mice (Hirai et al, 2007;Koch et al, 2008;van Vlies et al, 2007). In humans, treatment with insulin is associated with an increase in carnitine transport into and expression of OCTN2 in skeletal muscle (Stephens et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%